Awareness education of sport supporters on aggressiveness phenomena in sporting events / Tan Chee Hian … [et al.] - Tan, Chee Hian; Asmuni, Azizan; Md Sail, Rahim; Jong Young, Lee (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2019)
Study showed awareness education that learnt and performed by sport supporters were no matter whatsoever factors: Gender, Age, Higher Educational Institutions (HEIs) Attended, Types of sport, Favorite sports or Ethnicity were highly alert and aware especially on the phenomena of aggressiveness in sporting events. Supporters had learned skills of managing on those incidences were in good form as far as awareness education perspective was concerned where it involved sociological that emphasizing on “outside” of one person which involved surrounding of the person whom take part. As conclusion, the level of study among supporters played a vital factor to influent the awareness level among them toward aggressiveness phenomena in sporting events, this study managed to roundup several research questions with hypotheses investigated.